Menumbuhkan Rasa Percaya Diri Siswa Sekolah Dasar Melalui Permainan Bingo yang Menyenangkan dan Interaktif - Risma Hanifatur Rosyida; Silvia Dwi Anjelika; Idris Salam Septiyanto; Muhammad Nofan Zulfahmi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study discusses how bingo games can increase students' self-confidence at the primary school level. Bingo was chosen due to its interactive and fun nature, which is expected to create a learning environment that supports the development of students' self-confidence. This study aims to evaluate the effect of using bingo games on students' courage to actively participate in class. The approach used is a literature study, by reviewing various sources such as journal articles, books, previous research, and other relevant documents published in the last five years. The analysis process was carried out through the stages of collecting literature sources, categorizing data, synthesizing information, and drawing conclusions. The results of the literature review show that the implementation of bingo games in learning has significant potential in increasing students' confidence, which is reflected in the increased courage to speak in front of the class, actively answer questions, and interact with peers. This study concludes that bingo games can be an effective alternative learning method to develop elementary school students' self-confidence.